Pengembangan Gerak Motorik Kasar Melalui Senam Sehat Gembira Bagi Anak Usia Dini (Penelitian Tindakan Kelas Di Kelompok A Pendidikan Anak Usia Dini Miftahul Ulum Sukaresmi Garut) - Nurjani, Yan Yan; Tini, Ai (Jurnal Pendidikan Islam Anak Usia Dini : Anaking, 2024)
Kindergarten-aged children are generally very active, they have control over their bodies and are very fond of activities that they do on their own. Therefore, teachers need to provide space and time for children to do activities that can train children's gross muscles and provide items and equipment for children that can be pushed, lifted, released or carried. Growth during this period needs to be stimulated to receive information that is useful for children, as well as develop social-emotional attitudes. Along with brain growth, physical growth is important to pay attention to. An imbalance in physical growth will interfere with children's activities and physical motor abilities. The results of observations at PAUD Miftahul ulum Sukaresmi were found first, the lack of conducive learning process that took place. When educators are doing gymnastics, students tend not to be able to train their flexibility, balance and agility at the time of Second, students tend to be unable to do eye, foot, hand, and head movements in imitating gymnastics movements when the teacher is exemplifying.Third, students are not able to do physical games with the rules that have been set in healthy gymnasticsFourth, students have not shown skills in using the right and left hands. The purpose of this study is to get an overview of the effectiveness of the application of joyful healthy gymnastics on early childhood gross motor development in PAUD Miftahul Ulum Sukaresmi Garut and to get an overview of the significance of joyful healthy gymnastics as one of the methods of stimulating gross motor development in early childhood in schools. The research methodology used is a qualitative method, the type of research used is classroom action research (PTK) Data collection techniques with interviews, observations, documentation. Meanwhile, data analysis techniques are carried out data reduction, data exposure, and drawing conclusions. The object of this research is the development of early childhood gross motor skills through joyful healthy gymnastics, the subject of the research is PAUD Miftahul Ulum Sukaresmi Garut students totaling 20 students. The results of the data analysis showed that the application of joyful healthy gymnastics to early childhood gross motor development in group A PAUD Miftahul Ulum Sukaresmi Garut showed a significant impact related to the gross motor development of students, judging from the percentage results showing the final score, namely BB 0%, MB 0%, BSH 70% and BSB 30%, of course, these results after passing the pre-action,  Cycle I and Cycle II.  Keywords: Early childhood, Gross motor skills, happy healthy exercise